Relapse After Early-Stage, Favorable Hodgkin Lymphoma: Disease Characteristics and Outcomes With Conventional or High-Dose Chemotherapy. Issue 2 (10th January 2021) - Bröckelmann, Paul J.; Müller, Horst; Guhl, Teresa; Behringer, Karolin; Fuchs, Michael; Moccia, Alden A.; Rank, Andreas; Soekler, Martin; Vieler, Tom; Pabst, Thomas; Baues, Christian; von Tresckow, Bastian; et al.
Abstract : PURPOSE: We evaluated disease and treatment characteristics of patients with relapse after risk-adapted first-line treatment of early-stage, favorable, classic Hodgkin lymphoma (ES-HL). We compared second-line therapy with high-dose chemotherapy and autologous stem cell transplantation (ASCT) or conventional chemotherapy (CTx). METHODS: We analyzed patients with relapse after ES-HL treated within the German Hodgkin Study Group HD10+HD13 trials. We compared, by Cox proportional hazards regression, progression-free survival (PFS) after relapse (second PFS) treated with either ASCT or CTx and performed sensitivity analyses with overall survival (OS) from relapse and Kaplan-Meier statistics. RESULTS: A total of 174 patients' disease relapsed after treatment in the HD10 (n = 53) and HD13 (n = 121) trials. Relapse mostly occurred > 12 months after first diagnosis, predominantly with stage I-II disease. Of 172 patients with known second-line therapy, 85 received CTx (49%); 70, ASCT (41%); 11, radiotherapy only (6%); and 4, palliative single agent therapies (2%). CTx was predominantly bleomycin, etoposide, doxorubicin cyclophosphamide, vincristine, procarbazine, and prednisone (BEACOPP [68%]), followed by the combination regimen of doxorubicin, bleomycin, vinblastine, and dacarbazine (19%), or other regimens (13%). Patients aged > 60 years at relapse had shorter second PFS (hazard ratio [HR], 3.0; P = .0029) and were mostly treated with CTx (n = 33 of 49; 67%) and rarely with ASCT (n = 8; 16%). After adjustment for age and a disadvantage of ASCT after the more historic HD10 trial, we did not observe a significant difference in the efficacy of CTx versus ASCT for second PFS (HR, 0.7; 95% CI, 0.3 to 1.6; P = .39). In patients in the HD13 trial who were aged ≤ 60 years, the 2-year, second PFS rate was 94.0% with CTx (95% CI, 85.7% to 100%) versus 83.3% with ASCT (95% CI, 71.8% to 94.8%). Additional sensitivity analyses including OS confirmed these observations. CONCLUSION: After contemporary treatment of ES-HL, relapse mostly occurred > 12 months after first diagnosis. Polychemotherapy regimens such as BEACOPP are frequently administered and may constitute a reasonable treatment option for selected patients with relapse after ES-HL.